When Hanging on at All Costs is the Only Option - Walther-Broussard, Laura; Meyer, Tiffany; Nortjé, Nico (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2021)
Having hope that a terminally ill patient may recover is not an unfamiliar sight in intensive care units across the globe. However, cultural heritage may make it even tougher. This fictional case study, which is a collection of years of experience, addresses decision-making within the Chinese Immigrant culture and focusses on how this may influence the care team. A new initiative, the Goals of Care (GOC) team, is also described.